PERBEDAAN KEMANDIRIAN MAHASISWA S1 BIMBINGAN DAN KONSELING FKIP UKSW BERDASARKAN KEAKTIFAN DALAM KEGIATAN ORGANISASI DI KAMPUS - Febryan Cakrayudha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to see the significance of differences in the independence of Guidance and Counseling Study Program students based on their activeness in organizational activities on campus. This type of research is comparative research to compare the existence of one or more variables in two different samples, or at different times. The population in this study were UKSW FKIP Guidance and Counseling undergraduate students class 2020 - 2022. The sample in this study was 112 UKSW FKIP Guidance and Counseling students. This research data collection technique uses a Likert Scale. The data analysis technique used is Kruskal-Walls. The research results show that there is a significant difference between student independence based on their activeness in organizational activities on campus. proven by the results of the Asymp value analysis. Sig 0.000 < α= 0.05. Based on these results, it proves that there is a difference in the independence of UKSW FKIP Guidance and Counseling students based on their activeness in organizational activities on campus so that the hypothesis in this research is that Ho is rejected and H1 is accepted.